Strategic Dynamics and the Implications of Identity Politics in the 2024 General and Local Elections in Papua - Farid Al Hadana; Ratnaningrum Zusyana Dewi; Sakhidad Mahdiyar (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2026)
The 2024 General and Regional Elections in Papua serve as a critical focal point for understanding the evolving role of identity within Indonesia’s democratic contestation. This research seeks to decode the mechanisms through which political actors manufacture and institutionalize identity claims, while evaluating their subsequent effects on social cohesion and deliberative discourse. Adopting a qualitative-interpretive lens and an embedded comparative case study design, the study processes data from official records, political rhetoric, and social media via hybrid coding, discourse analysis, and process tracing. The results reveal a strategic shift: identity has moved beyond a quest for recognition to become a calculated electoral instrument that reinforces "us versus them" divisions. This transition is fueled by political brokers and digital amplification, creating a paradox where high mobilization success comes at the cost of intense social polarization and the delegitimization of democratic structures. By introducing a multi-level analytical framework that links actor strategies to institutional outcomes, this study argues that identity politics can be mitigated through the integration of inclusive local frameworks and the ethical values of tasamuh, shura, and ukhuwah.Pemilu Umum dan Pemilihan Daerah 2024 di Papua menjadi titik fokus penting untuk memahami evolusi peran identitas dalam dinamika demokrasi Indonesia. Penelitian ini bertujuan untuk mengurai mekanisme yang digunakan oleh para aktor politik dalam membentuk dan melembagakan klaim identitas, sekaligus mengevaluasi dampaknya terhadap kohesi sosial dan wacana deliberatif. Dengan mengadopsi lensa kualitatif-interpretatif dan desain studi kasus komparatif tertanam, penelitian ini mengolah data dari catatan resmi, retorika politik, dan media sosial melalui pengkodean hibrida, analisis wacana, dan penelusuran proses. Hasilnya mengungkapkan pergeseran strategis: identitas telah bergerak melampaui pencarian pengakuan untuk menjadi instrumen elektoral yang diperhitungkan yang memperkuat pembagian “kita versus mereka”. Transisi ini didorong oleh perantara politik dan amplifikasi digital, menciptakan paradoks di mana keberhasilan mobilisasi yang tinggi harus dibayar dengan polarisasi sosial yang intens dan delegitimasi struktur demokrasi. Dengan memperkenalkan kerangka kerja analitis multi-tingkat yang menghubungkan strategi aktor dengan hasil kelembagaan, penelitian ini berpendapat bahwa politik identitas dapat dimitigasi melalui integrasi kerangka kerja lokal yang inklusif dan nilai-nilai etis tasamuh, syura, dan ukhuwah.